Novel goose parvovirus in domestic Linwu sheldrakes with short beak and dwarfism syndrome, China. Issue 5 (17th July 2019) - Wan, Chunhe; Liu, Rongchang; Chen, Cuiteng; Cheng, Longfei; Shi, Shaohua; Fu, Guanghua; Chen, Hongmei; Fu, Qiuling; Huang, Yu
Abstract: Recently, short beak and dwarfism syndrome (SBDS) had a sudden outbreak in Cherry Valley duck flocks, followed by Pekin ducks and mule ducks in various regions of mainland China. This widely spreading infectious disease was characterized by growth retardation, smaller beak and tarsus with high morbidity and low mortality rate. In this study, we identified and characterized virus from domestic Linwu sheldrakes (namely as HuN18) with SBDS. HuN18 isolates shared high nucleotide identity with novel goose parvovirus (N‐GPV). A 5110‐nucleotide full‐length genome sequence of HuN18 was found with no deletion in ITR region. Alignment studies of HuN18 showed 96.8%–99.0% identity with other N‐GPVs and 92.9%–96.3% identity with classic GPV. According to the recombination analysis, HuN18 showed the potential major parent was the N‐GPV sdlc01 strain, the potential minor parent was the classical GPV Y strain, and the secondary potential minor parent was the SYG61v strain. To the best of our knowledge, this is the first report of N‐GPV in domestic Linwu sheldrakes with SBDS; these data provide evidence that attenuated live viruses are involved in genetic recombination with prevailing wild parvoviruses, which contributes to the novel emerging variants of waterfowl parvoviruses.